2012
DOI: 10.1097/rlu.0b013e31823ea42c
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Quantitative Perfusion and Functional Results and Acquisition Time With Reduced Administered Activity for 99mTc Tetrofosmin Myocardial Gated-SPECT

Abstract: Using about half of the activity recommended by the current diagnostic reference levels for separate-day myocardial perfusion imaging, the present study demonstrates that images may be obtained using ST protocol with quantitative results comparable with those from studies performed using the HT protocol, which is equivalent to an administered activity of 530 MBq. The former protocol would allow for a significant reduction of the dose to the patients as well as to the operators. Further studies are needed to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(17 reference statements)
1
4
0
2
Order By: Relevance
“…Since phase variables can be obtained fully automatically with high reproducibility [ 31 ], those can be readily incorporated into clinical PET-MPI reporting. In addition, phase entropy was consistently associated prognosis in patients undergoing SPECT and PET-MPI [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since phase variables can be obtained fully automatically with high reproducibility [ 31 ], those can be readily incorporated into clinical PET-MPI reporting. In addition, phase entropy was consistently associated prognosis in patients undergoing SPECT and PET-MPI [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A dissincronia do VE tem sido avaliada por várias modalidades de imagem cardiovascular, incluindo ecocardiograma com Doppler tecidual ou mesmo strain 18 , 19 ou ressonância magnética; 20 e imagem nuclear por meio de ventriculografia radioisotópica ou SPECT. 21 A contração do VE foi inicialmente analisada com sucesso por ventriculografia radionuclídica, mas, com a adição de análise de fase para gated SPECT e sua subsequente validação, esta técnica tem demonstrado excelente potencial na determinação da dissincronia mecânica do VE. A gated SPECT permite a avaliação da dissincronia do VE usando as funções harmônicas de Fourier para estimar o espessamento da parede ao longo do ciclo cardíaco e determinar o momento do início regional da contração mecânica do ventrículo, obtendo uma análise quantitativa tridimensional de todo o VE.…”
Section: Discussionunclassified
“…Os valores de corte de 135º para alargamento da banda (HBW) e 43º para o DP podem predizer a resposta clínica. 8 , 21 , 22 No presente estudo, encontramos uma média de 92,5º e 31º antes da ressincronização para HBW e DP de fase, respectivamente.…”
Section: Discussionunclassified
“…However, this study did not directly compare between standard dose and half dose data in the same group of patients. Another recent patient study 15 demonstrated that GSPECT using imaging dose with 31% reduction can yield comparable results to standard dose in terms of myocardial perfusion and left ventricular ejection fraction scores. A numerical observer study also suggested that there is some room to reduce either acquisition time or injected activity without degrading performance of myocardial perfusion defect detection using 3D reconstruction with better imaging models.…”
Section: Introductionmentioning
confidence: 95%